2006
DOI: 10.1063/1.2173240
|View full text |Cite
|
Sign up to set email alerts
|

Oriented barium hexaferrite thick films with narrow ferromagnetic resonance linewidth

Abstract: Hexagonal BaFe12O19 ferrite films, having thicknesses ranging from 200–500μm, were prepared by a screen printing process followed by sintering heat treatments. Structural, magnetic, and microwave measurements confirmed that the polycrystalline films were suitable for applications in self-biasing microwave devices in that they exhibited a large remanence (4πMr=3800G), high hysteresis loop squareness (Mr∕Ms=0.96) and low microwave loss. A derivative linewidth ΔH of 310 Oe was measured at 55.6 GHz. This represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 11 publications
3
53
0
Order By: Relevance
“…Ferrites, such as ferrimagnetic barium hexaferrite BaFe 12 O 19 (BaM), can play an important role in the propagation of electromagnetic waves in microwave and millimeter wave devices (such as tunable filters, phase shifters, and circulators) due to their low losses in the gigahertz frequencies and high magnetic anisotropy [347]. Growing thick films and multilayers of ferrite/ferroelectric (such as BaTiO 3 or PZT) compounds produces coupling of the magnetic response and ferroelectricity mediated by mechanical stress [348].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Ferrites, such as ferrimagnetic barium hexaferrite BaFe 12 O 19 (BaM), can play an important role in the propagation of electromagnetic waves in microwave and millimeter wave devices (such as tunable filters, phase shifters, and circulators) due to their low losses in the gigahertz frequencies and high magnetic anisotropy [347]. Growing thick films and multilayers of ferrite/ferroelectric (such as BaTiO 3 or PZT) compounds produces coupling of the magnetic response and ferroelectricity mediated by mechanical stress [348].…”
Section: Other Applicationsmentioning
confidence: 99%
“…For x=0.0, it exhibits 4πM s =3.78 kGs, and H a =17.6 kOe, which is similar to previously reported from bulk barium and strontium hexaferrite materials. 18,19 Furthermore, a higher LaCo concentrations leads to increasing magnetocrystalline anisotropy H a and otherwise lower saturation magnetization 4πM s . Such enhancements in H a could result in the shifting of observing FMR to higher frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to thin film growth, thick films (>10 lm) have also been demonstrated via spin coating 53 and printing 54 techniques with porosity levels acceptable for certain applications. It is also worth mentioning that Abe et al 55 has been reported on other complex oxide systems by the SSP technique.…”
Section: Csdmentioning
confidence: 99%